The Association of CD4+ T Cells Subsets with The Severity of Periodontitis: A Scoping Review - Nadiya Nurul; Devi Dwipriastuti; Endang Winiati Bachtiar (Faculty of Dentistry, Universitas Trisakti, 2025)
Periodontitis is a persistent inflammatory condition caused by a buildup of oral bacteria that damages the tissues around the teeth. It is defined by the deterioration of these tissues, which can result in tooth loss if not treated. The extent of periodontitis is influenced by various factors, including the host's immune response to bacteria that cause periodontal disease. Periodontal infections induce the differentiation of CD4+ T cells into various subsets, including Th1, Th2, Th17, Tregs, and other subsets. This review aimed to determine if there is an association between different subsets of CD4+ T cells and the severity of periodontitis. The research conducted a scoping review, which utilized the scoping review method to systematically map and analyze the literature results on the subject issue. The article search method employed Scopus, PubMed, and ScienceDirect databases, and a manual search was also conducted using keywords and the Boolean Operators technique. The publications were chosen based on the Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Review (PRISMA-ScR) flow, following the established criteria for inclusion and exclusion. As a result, 11 relevant publications were gathered and subsequently examined, focusing on the CD4+ T cell subsets in individuals with periodontitis. The publications show that individuals with periodontitis display a more prominent expression of subgroups of T cells. Moreover, the severity of periodontitis is strongly influenced by the host's immune response, particularly the balance between proinflammatory and anti-inflammatory CD4+ T cell subsets.